2021
DOI: 10.1093/trstmh/traa186
|View full text |Cite
|
Sign up to set email alerts
|

Value of C-reactive protein in differentiating viral from bacterial aetiologies in patients with non-malaria acute undifferentiated fever in tropical areas: a meta-analysis and individual patient data study

Abstract: C-reactive protein (CRP) is used to discriminate common bacterial and viral infections, but its utility in tropical settings remains unknown. We performed a meta-analysis of studies performed in Asia and Africa. First, mean CRP levels for specific tropical infections were calculated. Thereafter, individual patient data (IPD) from patients with non-malarial undifferentiated fever (NMUF) who were tested for viral and bacterial pathogens were analysed, calculating separate cut-off values and their performance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Erring on the side of caution to minimise the risk of missing cases that require antibiotics means that a relatively low cut-off value (like the 11 mg/L found here) may not have a huge impact on antibiotic prescriptions. Our findings are in line with a recent meta-analysis and individual patient data study [13], which showed that a CRP cut-off close to the one found here (10 mg/L) achieved very high sensitivity for bacterial infections. However, the optimal accuracy was found at 36 mg/L, and at a threshold of 40 mg/L the sensitivity and specificity for bacterial infections were 74% (95% CI 70-77) and 84% (95% CI 81-87), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Erring on the side of caution to minimise the risk of missing cases that require antibiotics means that a relatively low cut-off value (like the 11 mg/L found here) may not have a huge impact on antibiotic prescriptions. Our findings are in line with a recent meta-analysis and individual patient data study [13], which showed that a CRP cut-off close to the one found here (10 mg/L) achieved very high sensitivity for bacterial infections. However, the optimal accuracy was found at 36 mg/L, and at a threshold of 40 mg/L the sensitivity and specificity for bacterial infections were 74% (95% CI 70-77) and 84% (95% CI 81-87), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…10 This latter assertion is also supported by data from a study showing that a CRP level >40 mg/ml had a sensitivity of 74% for detecting bacterial infections in acutely febrile patients. 11 While such a multiplex test has not yet been developed, assessment of its potential costeffectiveness is essential to assist in guiding the research and policymaking processes that will underpin its successful development and implementation in the target settings. In this study, we aimed, therefore, to assess the cost-effectiveness in two tropical lower-middle income countries, one in Southeast Asia (Cambodia) and one in South Asia (Bangladesh), of a novel putative multiplex LF-RDT which measures CRP in addition to being able to diagnose acute enteric fever (e.g., by detecting typhoidal Salmonella antigens) and dengue (e.g., by detecting dengue NS1 antigen and dengue IgM) in patients with acute NMFI, in line with the results of the abovementioned Delphi survey.…”
Section: Introductionmentioning
confidence: 99%
“…10 This latter assertion is also supported by data from a study showing that a CRP level >40 mg/ml had a sensitivity of 74% for detecting bacterial infections in acutely febrile patients. 11…”
Section: Introductionmentioning
confidence: 99%